Preparation and Diagnosis of New Azo - Barbiturate Dyes - Kazim, Ali Ghazi; Kadhim, Abdullah Jawad (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2018)
The research includes the preparation of new azo-barbiturate dyes derived from shiff bases prepared by reaction Barbituric acid & phenlenediamine and repellency bases by means of double-reaction of repellant bases with different phenolic compounds. These compounds were diagnosed using infrared techniques, ultraviolet-visible radiation, NMR proton and thin layer chromatography. All barbiturate dyes had absorption between (273 – 310) nm and showed hypsochromic shift from the corresponding azo dyes. The crystal structures of barbiturate dyes indicated that barbiturate ring is sterically hindered by phenol rings .